The Effectiveness of Counseling using PLISSIT Model on Depression, Anxiety and Stress, among Postpartum Women with Sexual Dysfunction: A Randomized Trial - Farzaneh Karimi; Raheleh Babazadeh; Negar Asgharipur; Habibollah Esmaily; Robab Latifnejad Roudsari (Mashhad University of Medical Sciences, 2019)
Background & aim: Sexual dysfunction is common among women after childbirth, which could be associated with depression, anxiety and stress. The majority of these problems can be treated in early stages with different counseling approaches. The aim of this study was to assess the effect of counselling based on the PLISSIT model on depression, anxiety and stress among postpartum women with sexual dysfunction. Methods: This clinical trial was carried out on 80 women referred to urban healthcare centers of Mashhad, Iran in 2017, who had a score ≤ 28 based on the female sexual function index, with no history of sexual dysfunction before and during the pregnancy. They were randomly assigned to two groups of PLISSIT and control group. The subjects in the PLISSIT group attended two counseling sessions in two consecutive weeks and those in the control group received routine care. A demographic questionnaire, FSFI, as well as DASS-21 were used to measure female sexual function as well as depression, anxiety and stress before and 4 weeks after the last session in both groups. Data was analyzed using independent t-test, analysis of covariance, and Mann-Whitney U test. Results: The mean scores of DASS-21 total score were 9.6±7.5 and 3.3±2.9 in the PLISSIT group and 9.2±9.5 and 8.7±4.3 in the control group at the baseline and 4 weeks after the last session, respectively. The difference between means in two groups was significant (P=0.026). By controlling the intervening variables, the DASS-21 score in the intervention group decreased, compared to that in the control group. Conclusion: The PLISSIT model decreases the DASS-21 total score in women with sexual dysfunction after childbirth.